Modifications Of The Non-Linear Parameters Of The Heart Rate Variability Related To The Systematic Practice Of Physical Exercise - González-Velázquez, Victor Ernesto; Cobiellas-Carballo, Lázaro Ibraín; Rebustillo-Escobar, Roxana María; Semanat-Gabely, Walfrido; Bueno-Revilla, David de Jesús; López-Galán, Erislandis; Sánchez-Hechavarría, Miguel Enríquez; Escalante Batista, Salvador (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: In recent years, the relationship between the systematic practice of physical exercise, cardiovascular dynamics and the functioning of the autonomic nervous system has been recognized. Objective: To determine the modifications that non-linear parameters undergo in the autonomic cardiovascular regulation of the heart rate variability with the systematic practice of physical exercise. Methods: A retrospective cohort analytical study was conducted from February 2016 to August 2018. Population and sample: 36 individuals (Group 1: 18 high- performance baseball athletes; Group 2: 18 medical students). The data were collected in the Biomedical Basic Sciences Laboratory at Medical school 1, University of Santiago de Cuba, through the 8-channel PowerLab polygraph, and stored using the Kubios Software version 3.0.4 Premium. Results: Statistically significant differences between means were found in heart rate values (p = 0.000); SD1 (p = 0.025); SD2/SD1 ratio (p = 0.007); sample entropy (p = 0.011); short-term fluctuations α 1 (p = 0.019); mean line length (p = 0.016); max line length (p = 0.001); recurrence rate (p = 0.034); determinism (p = 0.010) and Shannon entropy (p = 0.015). The parameters of SD1 (C = 0.906) and sample entropy (C = 0.712) were significantly associated with a heart rate ≤ 70 beats per minute. Conclusions: With the systematic practice of physical exercise, the non-linear parameters of the autonomic cardiovascular regulation of the heart rate variability undergoes modifications that respond to a better adaptability of the autonomic nervous system, and to a greater capacity to regulate cardiovascular function.